The weather of before : versions of the Xhosa cattle killings in 1856 - McClenaghan, Kim (Department of English Language and Literature, 2014)
Every place has its own secrets. They lie just below the surface of the land, never quite sure of the story they might form. They are the unmentionables, the words that no one dares utter; but still they lie there, as part of a history that remains untold.